Global challenges facing plant pathology: multidisciplinary approaches to meet the food security and environmental challenges in the mid‑twenty‑first century - Jeger, Michael; Beresford, Robert; Bock, Clive; Brown, Nathan; Fox, Adrian; Newton, Adrian; Vicent, Antonio; Xu, Xiangming; Yuen, Jonathan (BMC, 2021)
The discipline of plant pathology has an expanding remit requiring a multi-faceted, interdisciplinary approach to capture the complexity of interactions for any given disease, disease complex or syndrome. This review discussed recent developments in plant pathology research and identifies some key issues that, we anticipate, must be faced to meet the food security and environmental challenges that will arise over coming decades. In meeting these issues, the challenge in turn is for the plant pathology community to respond by contributing to a wider forum for multidisciplinary research, recognising that impact will depend not just on advances in the plant pathology discipline alone, but on interactions more broadly with other agricultural and ecological sciences, and with the needs of national and global policies and regulation. A challenge more readily met once plant pathologists again gather physically at international meetings and return to the professional and social encounters that are fertile grounds for developing new ideas and forging collaborative approaches both within plant pathology and with other disciplines. In this review we emphasise, in particular: the multidisciplinary links between plant pathology and other disciplines; disease management, including precision agriculture, plant growth and development, and decision analysis and disease risk; the development and use of new and novel plant protection chemicals; new ways of exploiting host genetic diversity including host resistance deployment; a new perspective on biological control and microbial interactions; advances in surveillance and detection technologies; invasion of exotic and re-emerging plant pathogens; and the consequences of climate change affecting all aspects of agriculture, the environment, and their interactions. We draw conclusions in each of these areas, but in reaching forward over the next few decades, these inevitably lead to further research questions rather than solutions to the challenges we anticipate.